Suatu Kajian Literatur Masalah- Masalah yang Dihadapi dalam Mata Kuliah Jaringan Komputer - Mahesu Agni Zaus; Krismadinata Krismadinata (invotek, 2018)
Abstract— Computer network course is a subject that is the basic course that must be mastered by students majoring in Informatics Engineering. Practical and interesting learning has an interesting role in the learning process. Exciting learning can improve student learning outcomes and help students improve their understanding, as well as increase their motivation to improve their learning outcomes and knowledge. This article will discuss the problems related to computer network courses that are teaching methods and learning media. Based on the objectives of computer network courses it is proposed to optimize the content in teaching as well as on instructional media proposed to adopt software simulation for teaching to be interesting. Keywords: Computer Networking, Simulation, Teaching Method, Instructional Media